The widening gap between proclaimed gender equality and real state of affairs in times of COVID-19 pandemic - Vujadinović Dragica (Anali Pravnog Fakulteta u Beogradu)
A premise of this article is that the existing gap between the advanced gender equality normative framework and the state of gender equality in real life has widened in times of crises, including the COVID-19 pandemic. The background theoretical-methodological framework is presented in the introduction. The first chapter presents progressive gender equality achievements in the normative and strategic international, European and national framework. The next chapter explains why all crises have been worsening gender (in)equality in real life and even within the scope of already achieved rights. The third chapter outlines the negative impacts of COVID-19 on gender equality and living conditions of women globally, in the EU and Serbia. The fourth chapter addresses how the COVID-19 pandemic could contribute to advancing gender equality. The conclusion sums up the main topics of analysis and considers challenges related to the pandemic's possible positive impacts on gender equality.